TINJAUAN YURIDIS KASUS "BAU IKAN ASIN" GALIH GINANJAR DAN FAIRUZ A. RAFIQ - Musta'an, Habib (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2019)
The outbreak of the case of "salted fish" which involved Fairuz A. Rafiq with his ex-husband was a negative impact of technological advances. It began when Fairuz A. Rafiq's ex-husband, Galih Ginanjar, was interviewed by Rey Utami and Pablo Benua who alluded to Galih Ginanjar's household problems with his ex-wife, whose subsequent talk or interview was uploaded by Rey Utami and Pablo Benua on their youtube account . This case itself has so far dragged 3 (three) names as suspects, namely Galih Ginanjar, Rey Utami, and Pablo Benua. The purpose of this study is to know the legal rules that have been violated in the "salted fish" case (defamation) between Fairuz A Rafiq and Galih Ginanjar, and which articles can be applied for the case. This research uses legal research methods, based on a case approach (case approach), approach to legal doctrines (conseptual approach), historical approaches (historical approach), and approaches to existing legal rules (statute approach).